2020
DOI: 10.1016/j.ijscr.2020.09.094
|View full text |Cite
|
Sign up to set email alerts
|

Complete resection of rectal cancer with a synchronous solitary adrenal metastasis: A case report

Abstract: Highlights Adrenal metastasis is usually associated with systemic spread of the disease and is considered to be unsuitable for surgical resection. Adrenalectomy should be considered in patients who can undergo complete resection. Adrenalectomy may offer a better long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Although the surgical removal of metastatic CRC in the adrenal gland has not yet been widely practiced, surgical removal is being adopted in more patients, especially those with lung cancer and renal cell carcinoma. Recent research showed that adrenalectomy was an independent predictor of favorable survival in 14 patients with adrenal metastases from isochronous CRC, with 3 patients experiencing recurrence within 1 year of surgery and 6 patients surviving for >4 years after surgery [ 5 ]. Similarly, in our investigation, all of patients with CRC adrenal metastasis had a median survival time of 38.2 months after complete removal of the metastatic cancer; among the 13 patients, 3 survived for nearly 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgical removal of metastatic CRC in the adrenal gland has not yet been widely practiced, surgical removal is being adopted in more patients, especially those with lung cancer and renal cell carcinoma. Recent research showed that adrenalectomy was an independent predictor of favorable survival in 14 patients with adrenal metastases from isochronous CRC, with 3 patients experiencing recurrence within 1 year of surgery and 6 patients surviving for >4 years after surgery [ 5 ]. Similarly, in our investigation, all of patients with CRC adrenal metastasis had a median survival time of 38.2 months after complete removal of the metastatic cancer; among the 13 patients, 3 survived for nearly 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…3) статуса R0-операции; 4) безрецидивного периода 12-16 мес от момента операции на первичной опухоли [1,2,8,32].…”
Section: Discussionunclassified
“…(2020 г.) в 21% случаев отмечено развитие рецидивов заболевания в течение 1-го года после адреналэктомии [32].…”
Section: Discussionunclassified
See 1 more Smart Citation